IDENTIFIKASI MISKONSEPSI SISWA DENGAN MENGGUNAKAN METODE CERTAINTY OF RESPONSE INDEX (CRI) PADA MATERI PELAJARAN IPA - Evi Alfionitari; Nurlaeli Nurlaeli; Dini Afriansyah (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2019)
This study aims to reveal the misconceptions of students at the 46 Palembnag State Middle School in the "Human Circulatory System" material. The type of research used in this study is descriptive quantitative. Sampling was ditermined by  stratified Purposive Sampling.The research instrument used in this study was the Essay Problem accompanied by a Certainty of response index (CRI) column. The result showed that the percentage of students who experienced misconceptions was 28.3% and the percentage was smaller than the percentage of students who did not know the concept. The most common misconceptions experienced by students are the determination of blood groups, the scheme of the human circulatory system and the disturbances that occur in the human circulatory system. Keywords: CRI, Misconception, Human Circulatory System